Cross-Substitution of Δ(9)-Tetrahydrocannabinol and JWH-018 in Drug Discrimination in Rats - Wiley, Jenny L. (2014)
Synthetic indole-derived cannabinoids, originally developed to probe cannabinoid CB(1) and CB(2) receptors, have become widely abused for their marijuana-like intoxicating properties. The present study examined the effects of indole-derived cannabinoids in rats trained to discriminate Δ(9)-tetrahydrocannabinol (Δ(9)-THC) from vehicle. In addition, the effects of Δ(9)-THC in rats trained to discriminate JWH-018 from vehicle were assessed. Adult male Sprague-Dawley rats were trained to discriminate 3 mg/kg Δ(9)-THC or 0.3 mg/kg JWH-018 from vehicle. JWH-018, JWH-073, and JWH-210 fully substituted in Δ(9)-THC-trained rats and Δ(9)-THC substituted in JWH-018-trained rats. In contrast, JWH-320, an indole-derived cannabinoid without affinity for CB(1) receptors, failed to substitute for Δ(9)-THC. Pre-treatment with 1 mg/kg rimonabant significantly reduced responding on the JWH-018-associated lever in JWH-018-trained rats. These results support the conclusion that the interoceptive effects of Δ(9)-THC and synthetic indole-derived cannabinoids show a large degree of overlap, which is predictive of their use for their marijuana-like intoxicating properties. Characterization of the extent of pharmacological differences among structural classes of cannabinoids, and determination of their mechanisms remain important goals.